Antenatal Glucocorticoids in Low-Resource Settings—Who, When, and Where?. Issue 3 (25th September 2021) - Rouse, D.J.; Stringer, J.S.A.
Abstract : ( N Engl J Med . 2020;383:2584–2585) Glucocorticoid therapy has been long known to improve neonatal outcomes in preterm birth. The data supporting the use of antenatal glucocorticoids largely comes from high-resource countries. The Antenatal Corticosteroids Trial (ACT) published in 2015 investigated the use of antenatal dexamethasone in settings with limited access to obstetricians and neonatal intensive care. ACT found antenatal dexamethasone did not lower mortality among neonates with a birth weight below the fifth percentile (a proxy for preterm birth), but instead increased overall neonatal mortality compared with placebo (27.4 vs. 23.9 deaths/1000 live births) and increased the incidence of suspected maternal infection (3% to 2%).